In vitro anti- Helicobacterpylori , anti-urease and anti-gastric cancer activities of novel hydrazones - Maryam, Zahra; Kaya, Betul; Bostanci, Hayrani Eren; Kısa, Dursun; Celik, Ismail; Cevik, Ulviye Acar; Kaplancikli, Zafer Asim; Kısa, Dursun (Elsevier, 2024)
In this study, new hydrazone derivatives were synthesized by taking into account the virulence factor of the urease in the urease-positive microorganism H. pylori . The structure of synthesized compounds 3a -3j was confirmed using 1 H NMR, 13 C NMR and elemental analyses. After structure confirmations all compounds were evaluated for in vitro urease inhibitory and anti- H. pylori activities. Furthermore, since H. pylori infection is associated with gastric cancer, the effects of the synthesized compounds against two different gastric cancer cell lines (SNU1 and AGS) were also evaluated. Amongst the series, two compounds 3c and 3j were found to be excellent inhibitors of urease, having IC 50 values of 9.813 +/- 0.403 mu M and 11.407 +/- 0.393 mu M, better than the standard thiourea (IC 50 = 13.428 +/- 0.587 mu M), whereas the remaining compounds displayed moderate activity. Compounds 3c and 3d were found to be the most active in the series against H. pylori with MIC values 4 mu g/mL and 5 mu g/mL. Next, compounds were evaluated as anti-gastric cancer activity and the compounds 3c and 3j were more potent than reference drug cisplatin against SNU1 and AGS. The docking study was executed to analyzed the interaction between the active site of the urease and the compounds 3c and 3j . When the all activities (antiH. pylori , anti-urease and anti-gastric cancer activities) examined, it was found that the presence of the nitro group, which is an electron withdrawing group, in the 5th position of the thiophene ring (compound 3c ) increased all activities. From the structure-activity relationship, it has been observed that the compound 3c showed excellent potential for anti- H. pylori , anti-gastric cancer and can be alternative therapy in the future.
Keywords: Hydrazone; Urease; Gastric Cancer; Moleculer Docking; H. Pylori